2011
DOI: 10.1002/elan.201100118
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Nanoporous Iron (Hydr)oxide Electrode for Phosphate Sensing

Abstract: Nanoporous iron (hydr)oxide electrodes are evaluated as phosphate sensors using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The intensity of the reduction peak current (I cp ) of the ferrihydrite working electrode is tied to phosphate concentration at low pH; however, a hematite electrode combined with the use of EIS provided reliable sensing data at multiple pH values. Nanoporous hematite working electrodes produced an impedance phase component (q) that shifts with increasing pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…24 Furthermore, to develop calibration curves for arsenic, the normalized phase angle was plotted versus the -log of the arsenic concentration (M). A similar method was used in Moss et al 16,17 when developing a calibration curve for phosphate concentrations using EIS; in their work the phase angle was plotted versus the phosphate concentration. Equation 5 was used to calculate the normalized phase angles used in this paper:…”
Section: Influence Of Arsenic On Electrochemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, to develop calibration curves for arsenic, the normalized phase angle was plotted versus the -log of the arsenic concentration (M). A similar method was used in Moss et al 16,17 when developing a calibration curve for phosphate concentrations using EIS; in their work the phase angle was plotted versus the phosphate concentration. Equation 5 was used to calculate the normalized phase angles used in this paper:…”
Section: Influence Of Arsenic On Electrochemicalmentioning
confidence: 99%
“…This study showed that an increase in the arsenic concentration produced changes in the Nyquist plot that the authors attributed to an increase in the electron transfer resistance due to the adsorption of arsenic on the surface of the film. In another application of EIS for sensors, Moss et al 16,17 showed a correlation between phosphate concentrations (similar in chemistry to arsenate) and changes in phase angles at select frequencies. While these are a few examples that display the potential of using EIS as an analytical method in the water quality field, this technique has been given limited attention as an arsenic detection method and consequently little effort has been devoted to electrode material development for an arsenic sensor using the EIS technique.…”
mentioning
confidence: 99%
“…Bias voltages of −0.24 V and −0.28 V vs. SCE comparatively showed less pH dependence in a Bode phase diagram (data not shown), although −0.24 V vs. SCE might produce better resolution between log-unit C PO4 . In an earlier study, 29 −0.24 V vs. SCE was chosen as a bias voltage due to reliable correlation between phase and C PO4 at pH 7.00 at the frequency 0.2 Hz. In this work, when the same frequency and bias voltage were applied, the lin-log relationship between θ and C PO4 over the range 10 −8 -10 −4 M had a coefficient of correlation (R 2 ) greater than 0.930 over the pH range 6.75 -8.25.…”
Section: H108mentioning
confidence: 99%
“…28 We have found in our earlier study that nanoporous hematite coated electrodes are sensitive indicators of phosphate concentration using impedance and amperometric methods. 29 Analysis of the results of EIS experiments showed that there were changes in Bode phase diagrams that could be tied to phosphate concentration at pH 7 over the range 1 nM -0.1 mM (10 −9 -10 −4 M) in a 5 mM NaClO 4 electrolyte solution. Furthermore, we found that the intensity of a current peak in cyclic voltammograms had sensitivity to phosphate concentration at pH 4.…”
mentioning
confidence: 99%
“…[17,18] Also, great efforts have been devoted to designing hybrid-electrode materials for the detection of phosphate anions based on the modification of electrodes through electrochemical technique. [19][20][21] However, we developed an amperometric technique, which is sensitive to phosphate ions, and our method does not suffer from interference from arsenate or carbonate, which are known to limit the application of other methods of phosphate analysis.…”
Section: Introductionmentioning
confidence: 99%